2012
DOI: 10.2147/phmt.s37173
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effectiveness of the Wilbarger protocol with children

Abstract: Background: Sensory processing disorders have an estimated prevalence of 5%-10% in children without disability and 40%-88% in children with disability. A subtype of sensory processing disorder is sensory overresponsivity, which can result in fear, irritability, aggression, or avoidance behaviors in children. The Wilbarger protocol is the most prescriptive program used to treat sensory overresponsivity in children aged 2-12 years. Strong anecdotal evidence suggests that the Wilbarger protocol successfully reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…We outline the search strategy shown in Appendix A and adapted it for specific database characteristics. In addition, we hand searched the references of previous reviews (Baranek, 2002;Lang et al, 2012;MayBenson & Koomar, 2010;Schaaf & Blanche, 2011;Weeks, Boshoff, & Stewart, 2012) and included studies.…”
Section: Search Strategy For Identification Of Studiesmentioning
confidence: 99%
“…We outline the search strategy shown in Appendix A and adapted it for specific database characteristics. In addition, we hand searched the references of previous reviews (Baranek, 2002;Lang et al, 2012;MayBenson & Koomar, 2010;Schaaf & Blanche, 2011;Weeks, Boshoff, & Stewart, 2012) and included studies.…”
Section: Search Strategy For Identification Of Studiesmentioning
confidence: 99%
“…Salivary cortisol is produced in a typical diurnal fashion, with a peak just before waking and an evening nadir. This pattern is fixed in children by 4 to 6 years of age (Sumner, Bernard, & Dozier, 2010 (Weeks, Boshoff, & Stewart, 2012). This conclusion was drawn from the low number and poor methodological quality of available studies on this topic, rather than the presence of high quality evidence to refute its effectiveness (Weeks et al, 2012).…”
Section: Background and Literature Reviewmentioning
confidence: 98%
“…This pattern is fixed in children by 4 to 6 years of age (Sumner, Bernard, & Dozier, 2010 (Weeks, Boshoff, & Stewart, 2012). This conclusion was drawn from the low number and poor methodological quality of available studies on this topic, rather than the presence of high quality evidence to refute its effectiveness (Weeks et al, 2012). In the absence of high quality research, it is acknowledged that subjective anecdotal evidence, from occupational therapists and parents, support the efficacy of this approach for children in reducing their behavioral responses to environmental stimuli (Kimball et al, 2007 …”
Section: Background and Literature Reviewmentioning
confidence: 98%
“…The Wilbarger Approach is based on the premise that "individuals require a certain quality and quantity of sensory experiences to be skillful, adaptive and organized in their daily lives" (Wilbarger & Wilbarger, 2002, p 339). In a systematic review of the Wilbarger approach, Weeks, Boshoff, and Stewart (2012) found that the evidence so far has been drawn from small sample studies and has limited generalizability. Schaaf, Hunt, and Benevides (2012) suggest that the methodologies for evaluating the effectiveness of sensory-based interventions in randomized, controlled trials is improving through a method called Goal Attainment Scaling, which allows varied goals to be quantified on the same scale.…”
Section: Occupational Therapy Practice Frameworkmentioning
confidence: 99%